The Influence of Emotional and Spiritual Intelligence on Nurses’ Caring Behavior at the Universitas Sumatera Utara Hospital - Nurul Haflah; Jenny M. Purba; Nurmaini (STIKep PPNI Jawa Barat, 2022)
Aims: This study aims to analyze the influence of nurses’ emotional and spiritual intelligences on their caring behavior at the Universitas Sumatera Utara Hospital, Medan, Indonesia. Design: This research was designed cross sectionally. using simple random sampling, 126 nurses were selected as samples. Methods: Questionnaires of emotional intelligence, spiritual intelligence and caring behavior were then administered and analyzed using multiple linear regression. Results: The results showed a positive and significant effect of nurses’ emotional intelligence on their caring behavior (p = 0.001 < 0.05) as well as a positive and significant effect of nurses’ spiritual intelligence on their caring behavior (p = 0.008 < 0.05). It was found that the most dominant variable that affected caring behavior was the emotional intelligence variable. Conclusion: The findings of this study indicate that both hospital management and nurses need to carry out a few efforts to increase the nurses’ emotional and spiritual intelligence to achieve good caring behavior at the Universitas Sumatera Utara Hospital